Tanya Harmer, Beatriz Allende: A Revolutionary Life in Cold War Latin America, Chapel Hill, University of North Carolina Press, 2020, 384 páginas - Markarian, Vania (2022)
Fil: Markarian, Vania. Universidad de la República; Uruguay.